Effect of Fuel Subsidy Removal on Socio-Economic Development of Chanchaga Local Government Area of Niger State - Idris, Abu; Kitabu, Mohammed Umar; Musa, Muhammad Muhammad; Shehu, Ahmed (Kashere Journal of Politics and International Relations, 2024)
The removal of fuel subsidy in Nigeria raised a serious question among the citizens of it economic, social and environmental implications. This research work examines the effect of fuel subsidy removal on socio-economic development of Chanchaga Local Government. The study relied on quantitative approach to gather and analyzed its data. The study adopts Neo-liberalism theory. The study reveals that, fuel subsidy removal in Nigerian have affected citizens cost of living, income generation, employment level and security of lives and properties of people of Chanchaga Local Government Area of Niger State. The work therefore, recommends the following as measures to ensures balance in the economy even if the policy of subsidy removal has come to stay which include, government should implement targeted cash transfers or voucher programs to provide financial assistance to low-income households, helping them cope with the increased cost of living due to higher fuel prices, government should develop and promote alternative income-generating activities that are less dependent on fuel, such as sustainable agriculture, renewable energy projects, or skill-based cottage industries, to help citizens diversify their sources of income, government should establish vocational training programs and entrepreneurship initiatives to equip the unemployed with relevant skills and support them in starting small businesses or finding employment in sectors less affected by fuel prices, government should Enhance community policing efforts, improve street lighting, and implement crime prevention programs to address potential security concerns arising from increased economic hardship caused by higher fuel costs.